Comparative and clinical impact of targeted next-generation sequencing in pediatric pneumonia diagnosis and treatment - Shang, Hui; Zou, Sini; Ma, Zhanying; Liang, Qianyu; Zhong, Ye; Li, Ling; Chen, Qishan (Frontiers in Microbiology, 2025)
BackgroundCommunity-acquired pneumonia (CAP) remains a significant cause of pediatric morbidity and mortality worldwide. Conventional microbial tests (CMTs) frequently fail to accurately identify pathogens, especially in cases involving co-infections or less common organisms. Targeted next-generation sequencing (tNGS) presents a promising alternative, offering comprehensive pathogen detection.MethodsA retrospective observational analysis was conducted on 206 pediatric CAP patients from July 2021 to January 2023. Bronchoalveolar lavage fluid (BALF) samples underwent simultaneous tNGS and CMTs. Clinical diagnoses based on comprehensive analysis served as the reference standard. Relative abundance thresholds were optimized to reduce false-positive detections.ResultsTargeted next-generation sequencing detected pathogens in 97.0% (200/206) of cases, significantly higher than CMTs (52.9%, 109/206; p < 0.001). tNGS identified a broader spectrum of pathogens, substantially improving overall detection compared to CMTs (84.6% vs. 40.7%). Specifically, detection rates of viral pathogens (p < 0.05) and bacterial co-infections (p < 0.001) were significantly enhanced. The sensitivity and specificity of tNGS were 96.4 and 66.7%, respectively. Additionally, tNGS demonstrated superior diagnostic concordance with clinical diagnoses in both single and co-infection cases. Optimizing relative abundance thresholds reduced the false-positive rate from 39.7 to 29.5% (p < 0.0001). Clinical management was adjusted based on tNGS results in 41.7% of patients, significantly shortening hospital stays in severe CAP cases (p < 0.01).ConclusionTargeted next-generation sequencing provides significantly improved pathogen detection, especially for co-infections, compared to CMTs. Implementing standardized relative abundance thresholds enhances the diagnostic specificity of tNGS, supporting its integration into routine clinical diagnostics for pediatric CAP to facilitate precise, timely therapeutic interventions.